EVALUASI PERTUMBUHAN DAN PRODUKSI KARET BEBERAPA KLON INTRODUKSI DI WILAYAH BERIKLIM BASAH - Sayurandi Sayurandi (Institut Teknologi Sawit Indonesia, 2020)
The purpose of this study was to evaluate the growth performance and rubber production of some introduced rubber clones in wet climates. Exactly seven introduced clones were tested in this research by using randomized block design non factorial. The testing clones were planted in Aek Pamienke-Labuhan Batu Utara Regency in 2005. The rainfall average over past ten years were 3036 mm/year and number of rainy days average were 145 days/year. The parameters observed in this research were plant growth on immature period, rubber production, and leaf disease resistance. The reseacrh results showed that clone PB 330 and PB 340 had girth growth highest at five years old namely 53.90 cm and 50.20 cm, respectively. Based on rubber production showed that clone PB 330, PB 340, and PB 260 had highest rubber production (kg/tree/year) namely 4.75 kg, 4.80 kg and 4.70 kg, respectively. Based on the resistance of leaf disease showed that the introduced clones were moderate resistant to Oidium and resistant to Colletotrichum and Corynespora